Spontaneous rupture of a saphenous vein graft - Davey, P. (BMJ Group, 1999)
We present a case of spontaneous rupture of a right coronary bypass vein graft in a 57-year-old woman 10 years after coronary by-pass surgery. Although rare, this diagnosis should be considered in such patients presenting with appropriate symptoms.   Keywords: coronary artery bypass graft; false aneurysm; saphenous vein graft